Striatal spreading depolarization: Possible implication in levodopa‐induced dyskinetic‐like behavior. Issue 6 (13th February 2019) - de Iure, Antonio; Napolitano, Francesco; Beck, Goichi; Quiroga Varela, Ana; Durante, Valentina; Sciaccaluga, Miriam; Mazzocchetti, Petra; Megaro, Alfredo; Tantucci, Michela; Cardinale, Antonella; Punzo, Daniela; Mancini, Andrea; et al.
ABSTRACT: Objective: Spreading depolarization (SD) is a transient self‐propagating wave of neuronal and glial depolarization coupled with large membrane ionic changes and a subsequent depression of neuronal activity. Spreading depolarization in the cortex is implicated in migraine, stroke, and epilepsy. Conversely, spreading depolarization in the striatum, a brain structure deeply involved in motor control and in Parkinson's disease (PD) pathophysiology, has been poorly investigated. Methods: We characterized the participation of glutamatergic and dopaminergic transmission in the induction of striatal spreading depolarization by using a novel approach combining optical imaging, measurements of endogenous DA levels, and pharmacological and molecular analyses. Results: We found that striatal spreading depolarization requires the concomitant activation of D1‐like DA and N ‐methyl‐d ‐aspartate receptors, and it is reduced in experimental PD. Chronicl ‐dopa treatment, inducing dyskinesia in the parkinsonian condition, increases the occurrence and speed of propagation of striatal spreading depolarization, which has a direct impact on one of the signaling pathways downstream from the activation of D1 receptors. Conclusion: Striatal spreading depolarization might contribute to abnormal basal ganglia activity in the dyskinetic condition and represents a possible therapeutic target. © 2019 International Parkinson and Movement Disorder Society